Competing visions of empire : labor, slavery, and the origins of the British Atlantic empire - Swingen, Abigail Leslie (Yale University Press, 2015)
This title explores the connections between the origins of the English empire and unfree labour by exploring how England's imperial designs influenced contemporary politics and debates about labour, population, political economy, and overseas trade. It pays particular attention to how and why slavery and England's participation in the transatlantic slave trade came to be widely accepted as central to the national and imperial interest by contributing to the idea that colonies with slaves were essential for the functioning of the empire.